1999
DOI: 10.1182/blood.v93.2.590.402k11_590_598
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Dendritic Cell Subpopulations Present in the Spleen, Peyer’s Patches, Lymph Nodes, and Skin of the Mouse

Abstract: Dendritic cells (DC) are highly efficient antigen-presenting cells (APC) that have an essential function in the development of immune responses against microbial pathogens and tumors. Although during the past few years our understanding of DC biology has remarkably increased, a precise characterization of the different DC subpopulations remains to be achieved with regard to their phenotype and lineage relationships. In this report, we have extensively studied the DC subpopulations present in the thymus, spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 26 publications
7
95
0
1
Order By: Relevance
“…Increased CD8a and DEC205 expression on CD11c + CD11b À cells indicated that the majority of the remaining CD11c + cells present within the brain were similar phenotypically to lymphoid derived DC (CD11c + , CD11b À , CD8a + ) ( Fig. 1B) (Anjuere et al, 1999;Henri et al, 2001). Although the Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Increased CD8a and DEC205 expression on CD11c + CD11b À cells indicated that the majority of the remaining CD11c + cells present within the brain were similar phenotypically to lymphoid derived DC (CD11c + , CD11b À , CD8a + ) ( Fig. 1B) (Anjuere et al, 1999;Henri et al, 2001). Although the Fig.…”
Section: Resultsmentioning
confidence: 95%
“…CD11c + CD11b + cells isolated from the CNS of either CCL3 +/+ or CCL3 À/À mice expressed little to no CD8a or DEC205 suggesting a phenotype similar to myeloid derived DC (CD11c + , CD11b + , CD8a À , DEC205 À ) ( Fig. 1B) (Anjuere et al, 1999;Henri et al, 2001). Increased CD8a and DEC205 expression on CD11c + CD11b À cells indicated that the majority of the remaining CD11c + cells present within the brain were similar phenotypically to lymphoid derived DC (CD11c + , CD11b À , CD8a + ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16] The phenotype of DC recovered from the main conducting airways (AMDC) compares well with that of DC from the peripheral lung (LTDC). 13 Similarly, RTDC share some phenotypic traits with DC from other tissues such as the skin, 17 kidney, 18 liver 19 and gut, 20,21 particularly low expression of CD8a and high expression of CD205. However, such comparisons do more to enforce the notion that substantial heterogeneity exists among tissue DC populations.…”
Section: The Phenotype Of Mouse Rtdcmentioning
confidence: 99%
“…Most knowledge about human cDCs has been obtained from monocyte-derived DCs, but DCs in human tissues, particularly spleen DCs, have not been extensively characterized [8,9]. Buckley et al [10] showed that macrophages and DCs are located in the same splenic anatomical compartments and share monocyte-macrophage markers, suggesting that both cell types are related and possibly derived from a common precursor [10].…”
Section: Introductionmentioning
confidence: 99%